2008
DOI: 10.1136/bjsm.2007.046011
|View full text |Cite
|
Sign up to set email alerts
|

Perceived anxiety and plasma cortisol concentrations following rock climbing with differing safety rope protocols

Abstract: Objectives: To examine how different safety rope protocols impact on subjective anxiety and self-confidence levels and plasma cortisol concentrations and the relationship between subjective states and cortisol during rock climbing. Methods: Participants (n = 12) were tested in three climbing conditions that were designed to invoke low, moderate and high physical and mental stress. Plasma cortisol concentrations were collected before and after climbing and participants reported subjective anxiety and self-confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 10 publications
3
58
4
2
Order By: Relevance
“…Hardy and Hutchinson's (2007) first study demonstrated significantly greater Rating of Perceived Exertion (RPE), HR and RCAI measures of cognitive and somatic anxiety and activation, between an outdoor lead at a climbers limit minus two grades and at their on-sight limit; whilst Hardy and Hutchinson's (2007) third study showed significant elevation of cognitive anxiety and effort and reduction in activation and performance between a top-rope then top-rope climb and a lead then top-rope climb. Finally, Hodgson et al (2009) demonstrated significantly increased somatic anxiety and decreased self-confidence, as reported by the CSAI-2R, and increased plasma cortisol concentration between a top-rope and lead climb.…”
Section: Outline Of Climbing Psychophysiology Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Hardy and Hutchinson's (2007) first study demonstrated significantly greater Rating of Perceived Exertion (RPE), HR and RCAI measures of cognitive and somatic anxiety and activation, between an outdoor lead at a climbers limit minus two grades and at their on-sight limit; whilst Hardy and Hutchinson's (2007) third study showed significant elevation of cognitive anxiety and effort and reduction in activation and performance between a top-rope then top-rope climb and a lead then top-rope climb. Finally, Hodgson et al (2009) demonstrated significantly increased somatic anxiety and decreased self-confidence, as reported by the CSAI-2R, and increased plasma cortisol concentration between a top-rope and lead climb.…”
Section: Outline Of Climbing Psychophysiology Literaturementioning
confidence: 99%
“…The experience stated above, may differ from the experiences given in the original papers, as the abilities have been standardised, for ease of comparison, using the grading charts set out by Draper, Canalejo, et al (2011). It should also be noted that no indication of climbing grades were given by Hodgson et al (2009) Pijpers et al (2003), in lower-grade climbers by Hardy and Hutchinson (2007) and in intermediate climbers by Hodgson et al (2009). Pijpers et al (2003) found significantly greater heart rate (HR), movement entropy and blood lactate in high over low traverse conditions.…”
Section: Outline Of Climbing Psychophysiology Literaturementioning
confidence: 99%
See 3 more Smart Citations